African Swine Fever Virus A528R Inhibits TLR8 Mediated NF-κB Activity by Targeting p65 Activation and Nuclear Translocation - Xueliang Liu; Da Ao; Sen Jiang; Nengwen Xia; Yulin Xu; Qi Shao; Jia Luo; Heng Wang; Wanglong Zheng; Nanhua Chen; François Meurens; Jianzhong Zhu (Viruses, 2021)
African swine fever (ASF) is mainly an acute hemorrhagic disease which is highly contagious and lethal to domestic pigs and wild boars. The global pig industry has suffered significant economic losses due to the lack of an effective vaccine and treatment. The African swine fever virus (ASFV) has a large genome of 170–190 kb, encoding more than 150 proteins. During infection, ASFV evades host innate immunity via multiple viral proteins. A528R is a very important member of the polygene family of ASFV, which was shown to inhibit IFN-β production by targeting NF-κB, but its mechanism is not clear. This study has shown that A528R can suppress the TLR8-NF-κB signaling pathway, including the inhibition of downstream promoter activity, NF-κB p65 phosphorylation and nuclear translocation, and the antiviral and antibacterial activity. Further, we found the cellular co-localization and interaction between A528R and p65, and ANK repeat domains of A528R and RHD of p65 are involved in their interaction and the inhibition of p65 activity. Therefore, we conclude that A528R inhibits TLR8-NF-κB signaling by targeting p65 activation and nuclear translocation.